2019
DOI: 10.21203/rs.2.9721/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The midline approach for endotracheal intubation using GlideScope video laryngoscopy could provide better glottis exposure in adults: A randomized controlled trial

Abstract: Background: Previous studies have demonstrated that the common laryngoscopic approach (right-sided) and midline approach are both used for endotracheal intubation by direct laryngoscopy. Although the midline approach is commonly recommended for video laryngoscopy (VL) in the clinic, there is a lack of published evidences to support this practice. This study aimed to evaluate the effects of different video laryngoscopic approaches on intubation. Methods: Two hundred sixty-two patients aged 18 years who underwen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…In a sense, longer X2 distance caused by bucktooth and abnormal hard palate indicates shorter inter-incisor gap and smaller oral cavity space anatomically [15,16]. These two limiting factors further restrict the intraoral operation of laryngoscopy and create difficulty in exposing the glottis [17,18]. In this study, the optimal cut-off value of X2 was 30.1 mm (sensitivity = 76.9%, specificity = 76.9%), and this indicated that a X2 distance of more than 30.1 mm reminded us the application of assisted techniques during intubation more possibly and necessarily.…”
Section: Discussionmentioning
confidence: 99%
“…In a sense, longer X2 distance caused by bucktooth and abnormal hard palate indicates shorter inter-incisor gap and smaller oral cavity space anatomically [15,16]. These two limiting factors further restrict the intraoral operation of laryngoscopy and create difficulty in exposing the glottis [17,18]. In this study, the optimal cut-off value of X2 was 30.1 mm (sensitivity = 76.9%, specificity = 76.9%), and this indicated that a X2 distance of more than 30.1 mm reminded us the application of assisted techniques during intubation more possibly and necessarily.…”
Section: Discussionmentioning
confidence: 99%